2010
DOI: 10.1002/hlca.201000069
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Models for Discussing Additions to α,β‐Unsaturated Aldehydes Organocatalyzed by Diarylprolinol or Imidazolidinone Derivatives – Is There an ‘(E)/(Z)‐Dilemma’?

Abstract: Dedicated to Professor Henri Kagan on the occasion of his 80th birthdayThe structures of iminium salts formed from diarylprolinol or imidazolidinone derivatives and a,bunsaturated aldehydes have been studied by X-ray powder diffraction ( Fig. 1), single-crystal X-ray analyses (Table 1), NMR spectroscopy (Tables 2 and 3, Figs. 2 -7), and DFT calculations (Helv. Chim. Acta 2009Acta , 92, 1, 1225Acta , 2010 Angew. Chem., Int. Ed. 2009, 48, 3065). Almost all iminium salts of this type exist in solution as diaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
58
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 67 publications
0
58
0
6
Order By: Relevance
“…From the infrared spectral frequencies E s-cis and s-trans conformers of styrenes [2], polyenes [3], chalcones [4], unsaturated aldehydes [5], acid chlorides [6], unsaturated esters [7], gauche and anti-form acyl halides and its esters [8]. Nuclear magnetic resonance spectral chemical shifts was used for prediction of the spatial arrangement of protons such as cis and trans of organic stereo chemical compounds [9].…”
Section: Introductionmentioning
confidence: 99%
“…From the infrared spectral frequencies E s-cis and s-trans conformers of styrenes [2], polyenes [3], chalcones [4], unsaturated aldehydes [5], acid chlorides [6], unsaturated esters [7], gauche and anti-form acyl halides and its esters [8]. Nuclear magnetic resonance spectral chemical shifts was used for prediction of the spatial arrangement of protons such as cis and trans of organic stereo chemical compounds [9].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular note among these are the diarylprolinol ethers [10]. Significantly less work has been carried out to understand the reactivity of this class of catalyst, where the mode of asymmetric induction appears significantly more complex than that delineated for imidazolidinones [6].A substantial amount of data has been published to compare the relative reactivity of a number of different catalyst structures (including imidazolidinones and diarylprolinol ethers) for both cycloaddition and conjugate addition reactions [11]. It has also been shown that both proton affinity of the parent amine and LUMO energy level of the corresponding iminium ion can be used as useful ground state predictors of relative reactivity [12].…”
mentioning
confidence: 99%
“…Of particular note among these are the diarylprolinol ethers [10]. Significantly less work has been carried out to understand the reactivity of this class of catalyst, where the mode of asymmetric induction appears significantly more complex than that delineated for imidazolidinones [6].…”
mentioning
confidence: 99%
See 2 more Smart Citations